Accelerated 2D radial Look‐Locker T1 mapping using a deep learning‐based rapid inversion recovery sampling technique - Ahanonu, Eze; Goerke, Ute; Johnson, Kevin; Toner, Brian; Martin, Diego R.; Deshpande, Vibhas; Bilgin, Ali; Altbach, Maria (NMR in biomedicine, 2024)
Efficient abdominal coverage with T1‐mapping methods currently available in the clinic is limited by the breath hold period (BHP) and the time needed for T1 recovery. This work develops a T1‐mapping framework for efficient abdominal coverage based on rapid T1 recovery curve (T1RC) sampling, slice‐selective inversion, optimized slice interleaving, and a convolutional neural network (CNN)‐based T1 estimation. The effect of reducing the T1RC sampling was evaluated by comparing T1 estimates from T1RC ranging from 0.63 to 2.0 s with reference T1 values obtained from T1RC = 2.5–5 s. Slice interleaving methodologies were evaluated by comparing the T1 variation in abdominal organs across slices. The repeatability of the proposed framework was demonstrated by performing acquisition on test subjects across imaging sessions. Analysis of in vivo data based on retrospectively shortening the T1RC showed that with the CNN framework, a T1RC = 0.84 s yielded T1 estimates without significant changes in mean T1 (p > 0.05) or significant increase in T1 variability (p > 0.48) compared to the reference. Prospectively acquired data using T1RC = 0.84 s, an optimized slice interleaving scheme, and the CNN framework enabled 21 slices in a 20 s BHP. Analyses across abdominal organs produced T1 values within 2% of the reference. Repeatability experiments yielded Pearson's correlation, repeatability coefficient, and coefficient of variation of 0.99, 2.5%, and 0.12%, respectively. The proposed T1 mapping framework provides full abdominal coverage within a single BHP. Abdominal coverage in T1‐mapping methods typically used clinically is limited by the breath hold period (BHP) and the time needed for T1 inversion recovery sampling. We propose a slice‐selective radial Look‐Locker T1‐mapping framework utilizing rapid inversion recovery sampling, optimized slice interleaving, and deep learning to allow accurate T1 estimation of 21 slices within a 20 s BHP.